Hydrogen Isotope Effects on Aqueous Electrolyte for Electrochemical Lithium‐Ion Storage - Chou, Jia; Zhao, Yao; Li, Xue‐Ting; Wang, Wen‐Peng; Tan, Shuang‐Jie; Wang, Ya‐Hui; Zhang, Juan; Yin, Ya‐Xia; Wang, Fuyi; Xin, Sen; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2022)
As two stable hydrogen isotopes, protium and deuterium show magnified isotope effects in physicochemical properties due to the significantly varied atomic masses. In this work, aqueous electrolytes based on heavy water (D2O) and light water (H2O) were prepared to reveal the electrochemical isotope effects between the hydrogen isotopes. The covalent hydrogen–oxygen bond and intermolecular hydrogen bond in D2O are much stronger than those in H2O, making them thermodynamically more stable. Compared with the H2O‐based electrolyte, the D2O‐based electrolyte shows a broader electrochemical window, a higher percentage of coordinated water and a longer lifetime of hydrogen bond. Because of the above electrochemical isotope effects, the D2O‐based electrolyte shows high anodic stability against operation of high‐voltage layered oxide cathode materials including LiCoO2 and LiNi0.8Co0.1Mn0.1O2, which enables long cycle life and favorable rate performance of aqueous Li‐ion batteries. The electrochemical isotope effects between heavy water (D2O) and light water (H2O) were revealed to shed light on rational electrolyte design towards the realization of high‐performance aqueous Li‐ion batteries.